The Effect of Earplugs and Eye Masks Usage in the Intensive Care Unit on Sleep Quality: Systematic Review - Eda Polat; İkbal Çavdar; Kübra Şengör (Dubai Medical Journal, 2022)
Introduction: Patients in the intensive care unit (ICU) have severe and complex disease characteristics and their sleep problems should not be ignored. Poor-quality sleep is associated with impaired immune function and associated susceptibility to disease and infection, decreased energy levels, delirium, delays in recovery. This study is conducted to examine the results of studies examining sleep quality using earplugs and eye masks in the ICU. Methods: PubMed, Science Direct, Google Scholar, and Medline databases were scanned using “Earplugs, Eye masks, Sleep quality, Intensive care units” as keywords. For the search strategy, a query in a patient-intervention-compare-result (PICO) format was used. P: Patients in intensive care; I: Earplugs and eye mask; C: Noise, Light, and Sleep Quality; O: Using earplugs and eye masks improves sleep quality. Results: We included the 17 most eligible studies meeting defined inclusion/exclusion criteria involving 1,372 participants. Randomized controlled trial was used mostly as study design. The interventions within the scope of the studies were earplugs, eye masks, relaxing music, and quiet time protocol. Richard Campbell Sleep Questionnaire and Verran and Snydern Halpern Sleep Scale were the most used scale. Most of the studies reviewed found that the use of non-pharmacological interventions showed a significant improvement in sleep quality. Earplugs and eye masks were found to have potential positive effects on sleep quality and delirium incidence in ICU patients. Conclusion: The use of earplugs and eye masks is a noninvasive, economical, and effective way to improve sleep quality in adult ICU patients.